The effect of bio-chemical fertilizer on the growth perfomance of rubber seedlings / Norashikin Sa’ari - Sa’ari, Norashikin (Faculty of Plantation and Agrotechnology, 2018)
Rubber, Hevea brasiliensis, has been introduced in Malaysia ever since before independence in 1957. Being one of the major income in the economy of Malaysia, Today, Malaysia Rubber Board (MRB) has introduced more than 30 clones under the Rubber Research Institute of Malaysia (RRIM). The purpose of this study is to provide information about the effect of bio-chemical fertilizer on growth performance of the rubber seedlings and to study the best combination of fertilizer on the growth of rubber seedlings. The fertilizer used in this study are RISDA 1 fertilizer and RealStrong Bio-Chemical Compound Fertilizer. The clone selected is from latex timber clones under RRIM 2000 series which is RRIM 2002. The performance of the Hevea brasiliensis were measured in various aspect of parameters to determine the growth performance of the rubber seedlings. The experimental design used was Completely Randomized Design (CRD) with five replication. Five different combination of fertilizer were used; T1 (100% NPK) acted as control, T2 (60% NPK + 40% Bio-chemical fertilizer), T3 (40% + 60% Bio-chemical fertilizer), T4 (20% NPK + 80% Bio-chemical fertilizer) and T5 (100% Bio-chemical fertilizer). The results show that T2 had been the best combination fertilizer for the growth of RRIM 2002 seedlings compared to the other combination. . It show that combination of bio-chemical fertilizer with the NPK fertilizer does give positive effect in the growth rate of the rubber seedlings.